Effectiveness of Narrative Attachment-Based Therapy on Emotional Experience Towards Spouse and Family Executive Functioning Among Married Women - Hosseini Geravandi, Afsaneh; Asgari, Parviz; Yousefi, Zahra (Psychology of Woman Journal, 2023)
Objective: The present research aimed to investigate the effectiveness of Narrative Attachment-Based Therapy on emotional experience towards the spouse and family executive functioning among married women. Materials and Methods: This study was a quasi-experimental research with control and experimental groups, employing a pre-test, post-test, and follow-up design. The population consisted of all married women in Isfahan, among whom forty individuals were conveniently selected based on inclusion and exclusion criteria and randomly assigned into two groups, control and experimental (twenty individuals each). The research tools included scales for emotional experience towards the spouse and family executive functioning. While the control group was on a waiting list, the experimental group received eight sessions of Narrative Attachment-Based Therapy. Both groups responded to the research tools in three phases: pre-test, post-test, and follow-up. The collected data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (analysis of covariance). Findings: The results showed that Narrative Attachment-Based Therapy improved the dimensions of emotional experience towards the spouse and family executive functioning. Conclusion: Considering these results, it can be said that this method is suitable for improving family constructs, and counselors can benefit from it.